Assessing students’ comprehension and perceptions of a newly records management course in business technology management. - Abdul Karim, Zatul Himmah; Anual, Norazlan; Sauid, Muna Kameelah; Mustakim, Nurul Ain (Journal of Islamic, Social, Economics and Development, 2025)
Records management plays an important role in the systematic control and maintenance of both digital and physical records of business activities. Due to its importance, there is an increasing need for universities worldwide including Malaysia to expand the offerings of the records management course. To equipped future professionals with the necessary skills in handling records properly, formal education education is a must. This study was conducted to evaluate students’ perceptions on the newly introduced Records Management course in the Bachelor of Business Technology Management program. Specifically, the study aimed to examine students’ perceptions of the course’s value and assess their understanding of the key concepts following their first comprehensive test. A structured online questionnaire was used to collect data from 88 students regarding their understanding, perceived challenges and recommendation for enhancement. Out of 88 respondents, only 77 responses were recorded. Findings show that students found the course to be effective and relevant where they claimed strong engagement with improve understanding. However, they suggested the inclusion of more detailed explanations, real-world examples, hands-on activities and self- assessments to address complex topics effectively. Future study could explore longitudinal impacts of the course on professional performance, compare effectiveness across institutions, and evaluate the integration of digital tools and simulations in enhancing learning outcomes.